Review of the Research Articles - Haque, Anwar Ul (International Journal of Pathology, 2019)
The review of the research articles submitted for publication is a vital and critical element in crafting and maintaining quality of the journals. The reviewers play key role in selecting the articles which are useful, relevant to the objectives of the journal and of sound research quality. Two reviews are made mandatory by the Higher Education Commission of Pakistan for each article. Out of these two one should be preferably from a foreign country with good research standing. Proper review of the article and feedback to the authors not only go a long way for the quality of the journal but it also helps authors in improving his\her research methodology and writing ability.